The Ottoman Age of Exploration - Tzvi Langermann (International Institute of Islamic Thought, 2011)
This very interesting treatise describes in detail the expansion in the sixteenth century of the Ottomans south and east, from Yemen and Eritrea through the Indian Ocean and as far as Sumatra. Pivotal events were the Ottoman conquest of Egypt in 1517, which opened up for them the routes to Mecca, Medina, and points east—and their final expulsion from Yemen in 1636, depriving them of their key staging point in the area. The expansion took on various forms: the increase of military power (mainly naval), the development of economic interests, and the strengthening of ties with local Muslim populations. At times, the direction and initiative came directly from Constantinople—especially when the “Indian Ocean faction” was able to exert its influence—but more usually from Ottoman functionaries in Egypt and Yemen, or even ambitious pirates. The main rivals in the area were the Portuguese and their allies. However, developments elsewhere bore heavily on this contest, which, at times, took on global proportions. Ottoman interests in the Indian Ocean were strengthened by their role as guarantors of the Holy Cities and the pilgrimage routes to them, as well their defense of Muslim merchants throughout the area. For their part, the Portuguese viewed their affairs as part of a plan that would, they hoped, lead ultimately to the conquest of Egypt and the Holy Land. The Ottoman conquest of Iraq was at least in part an attempt to outflank the Portuguese and prevent a Portuguese-Safavid alliance. Ultimately, though, the protracted conflict with Persia launched by Murad III in 1577, apparently swayed by opponents of the Indian Ocean faction, seriously drained Ottoman resources, and was likely a factor in their ultimate failure to control the Indian Ocean. At various times the Ottomans considered joining forces with the French pirates or Dutch Protestants against the Portuguese. By the early seventeenth century, neither the Ottomans nor the Portuguese were contesting for dominance in the Indian Ocean; the key players there were the English, Dutch, Safavids, and Mughals ...